Visuelle und rechnergestützte Landnutzungskartierungen in einem komplexen tropischen Bergland - Ein Vergleich am Beispiel der West Usambara Berge in Tansania - Honecker, Ulrich; Löffler, Ernst (ERDKUNDE, 2001)
In the framework of the Tanzanian Resource Protection and Bufferzone Development Programme, land use and land cover of the West Usambara Mts were mapped. The West Usambaras constitute a highly complex mountain system both in terms of landuse/landcover and relief. In this paper the results of a visual interpretation of high quality CIR aerial photographs are compared with a computer based classification in order to show whether or under which circumstances digital classification can replace visual interpretation in an area of complex land use/land cover and high relief. The main advantage of the visual interpretation lies in the direct and correct identification of complex land cover classes. Difficulties, however, occur in the precise delineation of complex mapping units. The automatic classification, in contrast, produces a much more detailed delineation of mapping units giving the impression of greater mapping precision. However, the reliability of the classification is problematic because of a high proportion of mixed pixels. A considerable improvement of the classification can be achieved by using a digital elevation model as well as contextual knowledge (in this case agroecological zones). Both methods have advantages and shortcomings, however, as an operational method visual interpretation of aerial photographs will be difficult to replace, especially in areas of complex relief and land use/land cover.